FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI RSUD ARIFIN ACHMAD PEKANBARU TAHUN 2015: Factors Associated With Low Birth Weight Genesis (LBW) at Arifin Achmad Pekanbaru 2015 - Novia Nazirun (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2019)
Low Birth Weight Infants (LBW) or Infant Low Birth Weight (LBW) babies are born with birth weight less than 2500 g regardless of gestational age. Based on data of low birth weight (LBW) obtained from Arifin Achmad Hospital in 2013 stood at 130 cases of low birth weight of 2,848 deliveries, while in 2014 amounted to 169 cases of low birth weight of 1,613 deliveries and in 2015 stood at 257 cases of low birth weight and 722 bbln from 1680 deliveries. This study aims to determine the factors associated with the incidence of low birth weight (LBW) at Arifin Achmad Pekanbaru 2015. This research is a quantitative analytical study design types contol non mmatching case. Pupulasi is all infants born at Arifin Achmad Pekanbaru Year 2015. Cases are infants born weighing < 2500 and controls are babies born above > 2500 g. A sample of 1,680 people that is the case of 182 infants and 182 control babies randomly selected sampling. Data analysis was performed using univariate, bivariate and multivariate analyzes. Results of multivariate analysis: variables associated with low birth weight is maternal education (OR: 1,693; 95% CI: 1108-2586), spacing births (OR: 1586: 95% CI: 1027-2450) and anemia (OR: 1.540: CI 95 %: 1002-2368). Variable counfounding nothing in this study. Conclusion No association between maternal education, birth spacing and anemia with LBW. Advice for health care workers and agencies more actively provide counseling KIE and Capital actively seek information about LBW.